2008
DOI: 10.1179/136485908x278801
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology of toxocariasis in a rural settlement in São Paulo state, Brazil

Abstract: The seroprevalence of Toxocara canis and risk factors for infection with this parasite were explored in a rural settlement in São Paulo state, Brazil. Total IgA and IgE levels in 79 subjects were determined by turbidimetry and chemiluminescence, respectively. Total counts of leucocytes and erythrocytes and differential counts of leucocytes were made by flow cytometry. ELISA for the detection of anti-Toxocara IgG, IgA and IgE were standardized using Toxocara excretory-secretory antigens (TES) obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Josimo in the same area 15 . However, the soil contamination was evaluated by these authors in plots where at least one inhabitant had shown anti-Toxocara spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Josimo in the same area 15 . However, the soil contamination was evaluated by these authors in plots where at least one inhabitant had shown anti-Toxocara spp.…”
Section: Discussionmentioning
confidence: 95%
“…When soil samples were checked in 24 plots where at least one human being was considered seropositive, embryonated Toxocara spp. eggs were found in five (21%) of the investigated plots 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, the country has experienced increasing migration of people from cities to rural areas, most of them in poor living conditions and lacking sanitary infra-structure. 14,15 Emerging and re-emerging parasitic zoonoses such as toxocariasis, toxoplasmosis, and cysticercosis remain incontrollable in some regions. 6,8,16 Improved and new serological and molecular tests can represent an important tool in the attenuation of morbidity and mortality due to parasitic zoonoses, especially in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…These settlements are characterized by poor living conditions, deficient potable water supplies and sanitary facilities and could be a source for parasitic infections. 14,15 The Pontal of Paranapanema is one of the poorest and most undeveloped regions of the Sã o Paulo state, in southeastern Brazil. This region contains the highest density of rural settlements in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation